Soil beneficial microbes and their role in Sesbania grandiflora growth in non-fertile soil - Lalitha, S. (International Journal of Scientific Research and Management (IJSRM), 2015)
Soil bacteria are very important in bio geochemical cycles and have been used for crop production. Plant microbial interactions in the rhizosphere are the important to the plant health and also soil fertility. The supplemented nitrogen with Rhizobium and Glomus fasciculatum showed increased biomass (0.439 g plant-1), total nitrogen content (38.13 mg N g-1 dry plant) and phosphorus content (5.16 mg P g-1 dry plant) in dual inoculation at (200 mg N kg-1 of soil). Similarly, supplemental phosphorus in combination with dual inoculation significantly increased the biomass, total nitrogen content and phosphorus content followed by Rhizobium and Glomus fasciculatum inoculated plants. The nitrogen content was found to be higher in all dose rates of dual inoculated plants, specifically higher at 50 mg P kg-1 of soil (22.83 mg N g-1 dry plant). Dual inoculation with Rhizobium and Glomus fasciculatum increased the nodule nitrogenase activity (36-213%), dry matter yield (156-279%), total nitrogen content (12-159%) and total chlorophyll content of leaves of Sesbania grandiflora (125-395%) compared to the uninoculated control or single inoculation with either Rhizobium or Glomus fasciculatum alone. This study considered the impact of triple interaction involving Rhizobium Sg01, Glomus fasciculatum and Sesbania grandiflora on soil nutrients, soil enzymes and microbial dynamics.